2003
DOI: 10.2460/ajvr.2003.64.321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of inhibition of angiotensin converting enzyme with enalapril in dogs with induced chronic renal insufficiency

Abstract: Data suggest that inhibition of angiotensin converting enzyme was effective in modulating progressive renal injury, which was associated with reduction of glomerular and systemic hypertension and proteinuria but not glomerular hypertrophy. Inhibition of angiotensin converting enzyme may be effective for modulating progression of renal disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 39 publications
1
71
0
3
Order By: Relevance
“…Brown et al [11] found increases in glomerular pressure 1 month after 3/4 renal ablation, but blood pressure was not increased. However, these authors found increases in systolic and diastolic blood pressures 3 months after 11/12 renal ablation [10]. Thus, the development of hypertension may depend on what fraction of functioning nephrons is ablated.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Brown et al [11] found increases in glomerular pressure 1 month after 3/4 renal ablation, but blood pressure was not increased. However, these authors found increases in systolic and diastolic blood pressures 3 months after 11/12 renal ablation [10]. Thus, the development of hypertension may depend on what fraction of functioning nephrons is ablated.…”
Section: Discussionmentioning
confidence: 91%
“…Activation of the RAA system and development of hypertension in association with renal failure have been reported in cats [20,30,41]. In dogs, development of hypertension following partial renal ablation has been described [10,14]; however, involvement of the RAA system has not been verified by measuring the RAA system.In the present study, we examined whether hypertension would develop in dogs with experimentally induced chronic renal failure and evaluated the potential causal role of the RAA system. Renal ablation was used to prepare a canine model of chronic renal failure, and blood pressure was determined by telemetry, which causes minimum stress and allows continuous around-the-clock measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In dogs, a positive correlation between magnitude of proteinuria and time to uremic crisis or death has been reported 5. Additionally, an association between use of medications that typically cause a reduction in magnitude of proteinuria in patients with chronic kidney disease and improved renal outcome measures has been reported in human and veterinary patients 6, 7, 8, 9, 10, 11, 12. The urine protein : creatinine ratio (UPC) is a common method for assessing the magnitude of proteinuria in dogs, and strongly correlates with 24‐hours urine protein excretion 13.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, recent studies have shown that various therapeutic interventions, such as administration of angiotensin converting-enzyme inhibitors or dietary modifications, can reduce magnitude of proteinuria and slow progression of renal disease. [6][7][8][9] Because of such findings, veterinarians have begun to recognize potential benefits of reducing proteinuria in dogs with a variety of renal diseases, and treatment of dogs to reduce the magnitude of their proteinuria has been recommended. 4 Serial UPC monitoring is used to assess treatment efficacy, disease progression, and prognosis in proteinuric dogs.…”
mentioning
confidence: 99%